The Hierarchy of Earthquake and Tsunami: The Cases of Aceh, Nias, Bantul, Pangandaran, and Sunda Staits - Hardjono, Imam (Universitas Muhammadiyah Surakarta, 2006)
Indonesia is vulnerable to earthquake and tsunami disaster because it is located in the fracture zone between the continental and oceanic lithospheres, running from the west of Sumatera, though the south of Java, NTB, Sulawesi to Papua. In the theoretical framework of Indonesian tectonic lithosphere, this zone is known as Sula-spuur. The frequent earthquake and tsunamis in Indonesia justify the theory that the earth will always seeks for dynamic self-balance through oceanic basin as well as continental basement expansions. Based on the tectonic lithosphere analysis, the anatomy of earthquake and tsunami disaster in Java falls into two different paths. The first is northwestward path in Western Java following the Semangko fault trend, from Pangandaran/Cilacap through Kadipaten, Subang to Jakarta. The other is the northeastward path in Central Java and East Java running from Bantul through Prambanan, Klaten to Rembang. The two hats correspond to the seventeen-kilometre-deep-underground fracture involving basement rocks resulted from the area shifting evolution during the limestone age prior to the existence of limestone in Indonesia. Based on the evidences found in Bantul- Klaten earthquake, the question necessary to raise is whether similar earthquake may happen in Jakarta.